Peningkatan Eco Awareness melalui Edukasi pada Warga Desa Ranu Pani untuk Menguatkan Pemahaman pada Ancaman Bencana Alam - Lusy Asa Akhrani; Sukma Nurmala (Universitas Mathla'ul Anwar Banten, 2020)
INCREASING ECO AWARENESS THROUGH EDUCATION OF RANU PANI VILLAGERS TO STRENGTHEN UNDERSTANDING OF NATURAL DISASTERS THREATS. Ranu Pani is the last village at the foot of Mount Semeru. Villagers depend on agriculture for their livelihoods. However, the location of the village is in contact with the land of Bromo Tengger Semeru National Park (TNBTS) making residents unable to expand the agricultural area. The hilly contours and wrong farming methods make the sedimentation rate unstoppable. Ranu Pani village contour is hilly and has a large lake in the middle of the village as a village icon. Ranu Pani is the name of a large lake in the middle of settlements and agriculture, not far from Lake Ranu Pani there is Ranu Regulo which is more natural and avoid the sedimentation rate. The intervention was carried out by way of approaching and socializing awareness of water crisis and natural damage in the village. Participants are parents of guardians, and students in grades 4, 5 and 6 Ranu Pani One Roof Elementary School. Through this socialization, parents and children understand the threat of natural disasters in the next few years, in addition to the sedimentation rate, silting and narrowing of the lake that continues to occur as well as the threat of water crisis due to pollution of lake water from pesticides and the absence of waste management, while lake water is used as water consumed by citizens.